Upaya Meningkatkan Keaktifan Belajar Siswa Kelas X SMAK Gabriel Wanibesak dalam Pelajaran Sejarah dengan Menggunakan Metode Problem Based Learning - Primus Paskalius Seran; Antonius Bere; Clotilde Seran; Yuditha S. Kofi (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
Learning is essentially a process of interaction between students and educators and learning resources in a learning environment, according to Gagne (Kanusta 1977: 19). The purpose of this study was to measure the level of student activeness in the classroom by using the Problem Based Learning (PBL) learning method. Based on the results of observations that have been made by researchers in history learning activities in class X SMA Swasta Gabriel Wanibesak from 24 students, only 49% of students are active in learning history, this also shows that in cycle I the level of student learning activeness has a classical percentage level of 49% where this is further confirmed based on the formula for calculating student activeness criteria in learning according to Arikunto (2007: 18) If the level of activeness is below 75% then students are less active in participating in the teaching and learning process. In cycle II researchers used the Problem Based Learning (PBL) learning method, there was an increase in the level of student activeness where the level of activeness in cycle II classically averaged 83%, this shows the level of enthusiasm of students in participating in the teaching and learning process that occurs in the classroom, in cycle II the teacher also tries to guide students to be more active in the teaching and learning process, such as answering questions given by the teacher, being able to express opinions, students are also active in group discussions, students actively ask the teacher regarding the material that has been conveyed, with the help and guidance of the teacher so that in cycle II the average level of student activeness has increased well.